(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
The leaves of Bambusa vulgaris possesses several bioactivities and is used in traditional medicinal systems. However, its anti-diabetic activity has not been scientifically investigated so far. The present study was carried out to evaluate the anti-diabetic activity of petroleum ether extract of Bambusa vulgaris (family: Poaceae) leaves in Streptozotocin induced diabetic rats. The preliminary phytochemical study showed the presence of phytosterols and tannins. From the toxicity study it was observed that petroleum ether extract of Bambusa vulgaris (PEBV) was nontoxic up to the dose of 2000 mg/kg body weight. In this study, animals received continuous oral administration of PEBV for a period of 15 days at the doses of 200 mg/kg and 400 mg/kg body weight. The control group was administered distilled water for the same duration. The blood glucose level was determined by GOD-POD kit method. The effect of PEBV was compared with oral dose of 0.5mg/kg Glibenclamide. The results showed that the PEBV significantly lowered the fasting blood sugar level of hyperglycemic rats in a dose dependent manner and it was also comparable to that of the standard drug Glibenclamide.